Incidence and clinical implications of intraoperative BITA grafts conversion. Insights from the Arterial Revascularization Trial - Benedetto, U; Altman, D; Flather, M; Gerry, S; Gray, A; Lees, B; Taggart, D; on behalf of the ART investigators (Elsevier, 2018)
Background The arterial revascularization trial (ART) has been designed to answer the question whether the use of bilateral internal thoracic arteries (BITA) can improve 10-year outcomes when compared to single internal thoracic artery (SITA). In the ART, a significant proportion of patients initially allocated to BITA received other conduit strategies. We sought to investigate the incidence and clinical implication of BITA grafts conversion in the ART. Methods Among patients enrolled in the ART (n=3102), we excluded those allocated to SITA (n=1554), those who did not undergo surgery (n=16) and those operated on but withdrew after randomization (n=7). Propensity score matching was used to compare converted vs non-converted BITA groups. Results A total of 1525 patients were operated with intention to receive BITA grafting. Of those, 233 (15.3%) were converted to other conduit selection strategies. Incidence of conversion largely varied across 28 centres involved (from 0% to 42.9%). The most common reason for BITA grafts conversion was the evidence of at least one internal thoracic artery not suitable which was reported in 77 cases. Patients with intraoperative BITA graft conversion received a lower number of grafts (2.95±0.84 vs 3.21±0.74; P<0.001). However, hospital mortality rate was comparable to those who did not require BITA graft conversion (0 vs 1.6%; P=0.1) as well as the incidence of major complications. At 5 years we found a non-significant excess of deaths (11.9% vs 8.4%; P=0.1) and major adverse events (17.1% 13.2%; P=0.1) mainly driven by an excess of revascularization in patients requiring conversion. Conclusions The incidence of intraoperative BITA graft conversion is not irrelevant . BITA graft conversion is not associated with increased operative morbidity but its effect on late outcomes remain uncertain.